A Study of English Writing Problems of Undergraduate Students of Faculty of Humanities at Mahachulalongkornrajavidyalaya University, Nongkhai Campus, Thailand - Lun, Sovanda; Kanokkamalade , Veerakarrn; Klinchan, Nilratana (วารสารจิตวิทยาพุทธศาสตร์ประยุกต์เพื่อสังคม, 2021)
The purpose of this study were 1); to study the problems of English writing skill and 2); to seek the way to solve the problems of the English writing skill of Bachelor’s Degree students, Faculty of Humanities of Mahachulalongkorn rajavidyalaya University, Nong Khai Campus. This study was conducted by the means of questionnaire which 70 questions for the 47 students Statistical devices used in the data analysis were frequencies, percentages, means and standard deviations. The problems in English writing found that the students faced the most difficulties in English writing were grammar section, which were totaled rate at high levels ( Mean = 4.09, S.D. = 1.51). The ways to solve the problems, it found that the first section of the ways to solve the problems were spelling section, which were totaled rate at high levels (Mean = 4.24, S.D. = 1.38). According to the analysis of all the information above the researcher absolutely sure that those information were fact and both of the problems and the ways to solve the problems of English writing skill of the students would be one source for the future works of many researchers who need some of those information because English writing skill is also one of the very important in the world.